UJI KINERJA MESIN PENIRIS MINYAK GORENG PADA PENGOLAHAN KERIPIK - Hamimi Hamimi; Tamrin Tamrin; Sri Setyani (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2011)
This study was aimed to test the performance of ‘AGROWINDO’ cooking oil spinner by determining the best spinning rate and spinning duration on several types of chips processed at home-industry scale. The research was conducted in two factors : the spinning rate (rpm) 1: 4 = 400, 1:5 = 450, and 1:6 = 500 rpm, and the duration of spinning time: 40, 60, and 80 seconds; cassava chips, banana chips, and sweet potato chips were used as materials. The treatments were replicated three times. The data of cooking oil drained or removed from the chips and the amount of rejected chips were analyzed descriptively, while the data obtained from organoleptic test of the chips were analyzed using ANOVA, then continued tested using orthogonal polynomials at 1% and 5% levels. The results of this study indicated that: the spinning rate (rpm) and spinning duration had an effect on level of disposal cooking oil and amount of rejected chips. The highest level of cooking oil removed from the chips was found at sweet potato chips with value of 19.5%. This value was obtained through spinning rate of 500 rpm and spinning duration of 80 seconds.